Vegetable Seed Bed Preparation on Phosphatic Clays - Edward A. Hanlon; George J. Hochmuth; Lawrence Shaw; Charles W. Riddle (EDIS)
This document addresses tillage associated with vegetable production on reclaimed phosphatic clays and summarizes the research findings from the Mined Lands Research/Demonstration Project (MLRDP), a cooperative project involving the University of Florida Institute of Food and Agricultural Sciences (UF/IFAS), Florida Institute of Phosphate Research (FIPR), the Polk County Board of Commissioners, and the phosphate industry. This project functioned from 1985 through 1994. This document is intended for growers, land managers, and mining industry land-use planners and assumes a familiarity with basic soil tillage and vegetable horticultural processes. This document is SL223, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Originally published as SS-MLR-4 in June 1993. Revised March 2005 as SL223.